2015
DOI: 10.1155/2015/175726
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aqueous Leaf Extract ofCardiospermum halicacabum(L.) on Fertility of Male Rats

Abstract: Treatment with 100 mg/kg and 200 mg/kg body weight of aqueous leaf extract (ALE) of Cardiospermum halicacabum for 30 days produced a significant dose dependent increase in the sperm counts and sperm motility in both caput and cauda regions. Further, significant increase in serum testosterone level was evident at all applied doses. However, no significant changes in the weight of sex organs were observed. Aqueous leaf extract also increased the number of females impregnated, number of implantations, and number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…An activity decreased of enzymes in the liver has been related to cytolysis processes and the consequent release of them into the blood stream (Bacchetta et al, 2011;Bhattacharya et al, 2008). It had been shown that toxic effects due pesticides exposure can be reversed by treating with herbal formulations (Peiris et al, 2015). Finally, it can be concluded that exposure of rats to functions were decreased with exposure of Judo 40 could result in increase PCV, WBC parameters and liver damage.…”
Section: Discussion:-mentioning
confidence: 99%
“…An activity decreased of enzymes in the liver has been related to cytolysis processes and the consequent release of them into the blood stream (Bacchetta et al, 2011;Bhattacharya et al, 2008). It had been shown that toxic effects due pesticides exposure can be reversed by treating with herbal formulations (Peiris et al, 2015). Finally, it can be concluded that exposure of rats to functions were decreased with exposure of Judo 40 could result in increase PCV, WBC parameters and liver damage.…”
Section: Discussion:-mentioning
confidence: 99%
“…Moreover, the difference between the age groups and the degree of knowledge of respondents about the uses of medicinal plants for the treatment of this reproductive health problem was significant (P < 0.05). Older respondents (40-60) had more knowledge than less aged respondents (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Socio-demographic Characteristics Of the Informantsmentioning
confidence: 99%
“…Rosmarinus officinalis [25]; Ficus carica [26]; Tribulus terrestris [27,28]; Cardiospermum halicacabum [29]; Urtica dioica L. [30]; Camellia sinensis [31]; Withania somnifera [32] etc… Benin, a West African country, has an interesting ethnopharmacological potential. The investigation of Adjanohoun et al [33] documented nearly 501 plant species and that of Akoègninou et al [34] identified 2807 plant species.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43] Some research has shown antimalarial activity of the extracts of this plant as well as anti-inflammatory and analgesic, antiparasitic, anti-diarrheal, anti-diarroil, antihysterility, anti-sterility, nephroprotective; hepato-protective and anticancer activity. [44][45][46][47][48][49][50][51][52]…”
Section: Pharmacological Activitymentioning
confidence: 99%